Synthesis, biological evaluation and docking studies of trans‐stilbene methylthio derivatives as cytochromes P450 family 1 inhibitors. (18th July 2017) - Wierzchowski, Marcin; Dutkiewicz, Zbigniew; Gielara‐Korzańska, Agnieszka; Korzański, Artur; Teubert, Anna; Teżyk, Artur; Stefański, Tomasz; Baer‐Dubowska, Wanda; Mikstacka, Renata
Abstract : Cytochromes P450 family 1 (CYP1) are responsible for the metabolism of procarcinogens, for example polycyclic aromatic hydrocarbons and aromatic and heterocyclic amines. The inhibition of CYP1 activity is examined in terms of chemoprevention and cancer chemotherapy. We designed and synthesized a series of trans ‐stilbene derivatives possessing a combination of methoxy and methylthio functional groups attached in different positions to the trans ‐stilbene skeleton. We determined the effects of synthesized compounds on the activities of human recombinant CYP1A1, CYP1A2 and CYP1B1 and, to explain the variation of inhibitory potency of methoxystilbene derivatives and their methylthio analogues, we employed computational analysis. The compounds were docked to CYP1A1, CYP1A2 and CYP1B1 binding sites with the use of Accelrys Discovery Studio 4.0 by the CDOCKER procedure. For CYP1A2 and CYP1B1, values of scoring functions correlated well with inhibitory potency of stilbene derivatives. All compounds were relatively poor inhibitors of CYP1A2 that possess the most narrow and flat enzyme cavity among CYP1s. For the most active CYP1A1 inhibitor, 2‐methoxy‐4′‐methylthio‐ trans ‐stilbene, a high number of molecular interactions was observed, although the interaction energies were not distinctive. Abstract : A series of trans ‐stilbene derivatives possessing a combination of methoxy and methylthio functional groups were synthesized in order to evaluate the influence of the structure variations on the affinity of ligands to CYP1 cytochromes. We attempted to elucidate the diversified inhibitory activities of polymethoxy/methylthio trans ‐stilbenes with the use of computational methods. Docking studies showed a good correlation between experimental data and predicted affinities for CYP1A2 and CYP1B1 giving insight into essential interactions of trans ‐stilbenes in CYP1 binding sites.